2000
DOI: 10.1002/1521-2254(200011/12)2:6<477::aid-jgm137>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Role of endosomes in gene transfection mediated by photochemical internalisation (PCI)

Abstract: Photochemical transfection occurs through endocytosis, followed by cytosolic release of the transfecting DNA from photochemically permeabilised endocytic vesicles. Release of plasmid from early endosomes seems to be of importance in photochemical transfection, although a role of later endocytic vesicles can, however, not be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 43 publications
7
50
1
Order By: Relevance
“…It was demonstrated that photochemical treatment, inducing permeabilization of the endocytic vesicles and liberation of the entrapped transfecting genes, can substantially increase the efficiency of gene transfection mediated by nonviral vectors. 24,25 However, in spite of significant increase, they were not able to transfect the entire population of cells compared to the results obtained for photochemically enhanced adenovirus-mediated gene delivery. 26 By relying on the idea that the effectiveness of nonviral transfection systems depends on the cell cycle status, 27 they investigated the role of the cell cycle status in photochemical transfection mediated by two types of synthetic transfection agents: a cationic polypeptide polylysine (polyfection) and a cationic lipid formulation N-(2-amino ethyl)-N,N-dimethyl-2,3-bis(tetradecyloxy)-1-propanaminium bromide/dioleoylphosphatidyl ethanol amine.…”
Section: Intelligent Polymeric Vectors In Gene Therapymentioning
confidence: 83%
“…It was demonstrated that photochemical treatment, inducing permeabilization of the endocytic vesicles and liberation of the entrapped transfecting genes, can substantially increase the efficiency of gene transfection mediated by nonviral vectors. 24,25 However, in spite of significant increase, they were not able to transfect the entire population of cells compared to the results obtained for photochemically enhanced adenovirus-mediated gene delivery. 26 By relying on the idea that the effectiveness of nonviral transfection systems depends on the cell cycle status, 27 they investigated the role of the cell cycle status in photochemical transfection mediated by two types of synthetic transfection agents: a cationic polypeptide polylysine (polyfection) and a cationic lipid formulation N-(2-amino ethyl)-N,N-dimethyl-2,3-bis(tetradecyloxy)-1-propanaminium bromide/dioleoylphosphatidyl ethanol amine.…”
Section: Intelligent Polymeric Vectors In Gene Therapymentioning
confidence: 83%
“…As described in our earlier work PCI constitutes an efficient and light -inducible method for in vitro transfection with plasmid /polylysine complexes. 3,4,8,9 Unfortunately, plasmid / polylysine complexes are very poor agents for in vivo gene delivery. 10 In contrast, adenoviruses are known to be efficient vectors for in vivo gene delivery.…”
mentioning
confidence: 78%
“…Interestingly, the photochemical treatment could not counteract the decrease in transgene expression observed at high amounts of polycations. Previous studies suggest that the PCI technology only act intracellularly, 23,24 and thus a possible attenuation of the viral uptake due to aggregate formation would not be counteracted by the photochemical treatment. Some of the decrease in transduction may, however, be attributed to cellular toxicity at high PLL concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…21 The mechanism and benefit of the technology has earlier been documented for nonviral vectors. [22][23][24][25] In this work, the effect of photoactivation of the photosensitizer TPPS 2a (meso-tetraphenylporphine with two sulfonate groups on adjacent phenyl rings) on adenoviral transduction in the presence of the polycationic agents poly-L-lysine (PLL) and SuperFectt is investigated. Our results show that the combined use of polycations and photochemical treatment greatly enhance transduction, especially in cells expressing moderate to low levels of CAR.…”
Section: Introductionmentioning
confidence: 99%